Women's Political Parties in Europe. Issue 1 (23rd March 2016) - Cowell-Meyers, Kimberly
Abstract : In representative democracies, political parties organize the public will, giving expression to political differences in society (see Katz and Mair 1995; Klingemann, Hofferbert, and Budge 1994; Sartori 1967). Parties can also deepen democracy by broadening the connections between representatives and constituents, helping to hold political institutions accountable and increasing the participation of previously marginalized groups (see Costain 2005; Kitschelt 1993; Shugart 1994; Kittilson and Tate 2005; Young 2000).